Sino-European Relations During Donald Trump’s Second Term - Goulard, Sebastien (Theoretical and Practical Research in Economic Fields, 2025)
The United States' tariff threats - and their subsequent enforcement - have ramifications that extend well beyond bilateral trade relations. They disrupt the global trading system as a whole. During his second term, President Donald Trump planned to extend new tariffs to the world’s two other major trading blocs: China and the European Union. These two powers, already embroiled in mutual trade tensions, had imposed tariffs on selected goods from one another. In this context, a key question arises: to what extent has the U.S.-driven trade war influenced the course of Sino-European trade negotiations? Has it compelled both parties to reassess their strategies and move toward closer coordination? By examining the decisions taken by China and the EU, especially in comparison to the positions adopted during Trump’s first term, we observe a notable hardening of positions on several fronts. Both actors, though long-time advocates of free trade, have shifted away from this principle under increasing geopolitical and economic pressure. While U.S. influence partly explains the EU’s firmer stance toward China, the trend reflects a deeper and more enduring transformation in Sino-European trade relations.